PVCS/GO nanocomposites: investigation of thermophysical, mechanical and antimicrobial properties. (4th July 2022) - Sheydaei, Milad; Pouraman, Vahid; Alinia-Ahandani, Ebrahim; Shahbazi-Ganjgah, Shabnam
Abstract : In this study, polyvinyl chloride (PVC) was modified using sodium trisulfide (Na2 S3 ) and ethanol, and sulfur was successfully incorporated into the structure. Then, nanocomposites were prepared by added graphene oxide (GO). The modified PVC (PVCS) characteristics were investigated by Fourier transform infrared (FTIR), Raman spectroscopy, X-ray diffraction (XRD), proton nuclear magnetic resonance ( 1 H NMR), and differential scanning calorimetry (DSC). Also, the nanocomposites were investigated by scanning electron microscopy (SEM), FTIR spectroscopy, XRD, and DSC. Moreover, the mechanical and antimicrobial properties of the samples were investigated. The presence of sulfur in the structure created antimicrobial properties but slightly reduced the mechanical and thermophysical properties. Sulfur can disrupt important intermediate metabolites in mitochondria by forming hydrogen sulfide. Hence, PVCS showed inhibitor and killing against Bacillus subtilis and Staphylococcus aureus, but in Escherichia coli and Shigella dysenteriae at concentrations used PVCS only the ability to kill them was observed. According to the results, PVCS is more effective against gram-positive bacteria than gram-negative. The addition of GO to the structure improved the mechanical, thermophysical as well as antimicrobial properties to the extent that the inhibition zone was observed in Escherichia coli and Shigella dysenteriae . GRAPHICAL ABSTRACT: UF0001